Grit, Self-Efficacy, Motivation and the Readiness to Change Index Toward Exercise in the Adult Population - De La Cruz, Manuel; Zarate, Alex; Zamarripa, Jorge; Castillo, Isabel; Borbon, Angelica; Duarte, Hector; Valenzuela, Kathryn (Frontiers in Psychology, 2021)
This study examined the relationships between grit personality, self-efficacy, motivation (autonomous, controlled, and amotivation), and the readiness to change index toward exercise. Participants were 391 adults aged between 18 and 64 years old (M = 31.16; SD = 12.45) from Hermosillo, Sonora (Mexico) who completed questionnaires (i.e., the Grit Personality Scale, the Exercise Self-Efficacy Questionnaire, the Treatment Self-Regulation Questionnaire and the Stages of Change Questionnaire for Physical Activity) measuring the variables of interest. The reliability of the instruments was tested using Cronbach’s alpha, whereas confirmatory factor analyses were performed for each instrument separately. A measurement model and a structural equation model were assessed as well. The results of the structural equations model showed that grit personality was positively associated with self-efficacy, and, in turn, with autonomous motivation and with the readiness to change index. On the other hand, self-efficacy was negatively correlated with controlled motivation, and positively correlated with the readiness to change index. Finally, self-efficacy also showed a negative correlation with amotivation, which, in turn, was negatively correlated with the readiness to change index. These results provide information to develop psychological intervention programs based on grit personality and motivation, with the aim of increasing the number of participants who engage in exercise.